Robot-assisted minimally invasive esophagectomy versus video-assisted thoracoscopic esophagectomy versus open esophagectomy for locally advanced esophageal cancer after neoadjuvant therapy: a systematic review and network meta-analysis - Zhou, Yufei; Zheng, Qiangqiang; Zhou, Yunfeng; Liu, Xiong; Chen, Wei; Lu, Yusong; Yuan, Yang (Frontiers in Oncology, 2025)
BackgroundEsophageal cancer (EC) remains a lethal malignancy with poor survival outcomes despite multimodal therapy. While minimally invasive techniques like video-assisted thoracoscopic esophagectomy (VATE) and robot-assisted minimally invasive esophagectomy (RAMIE) have gained traction over open esophagectomy (OE), their comparative safety, efficacy, and survival benefits in patients receiving neoadjuvant therapy remain underexplored.MethodsWe conducted a Bayesian network meta-analysis on data from seven studies (n=1847 patients) to compare OE, VATE, and RAMIE after neoadjuvant therapy for locally advanced EC. Outcomes included complication rates, operative time, R0 resection, lymph node yield, and 3-year overall survival (OS).ResultsNo significant differences were observed in R0 resection rates (RAMIE vs. OE: OR = 1.03, 95% CI 0.25–4.70; VATE vs. OE: OR = 1.37, 0.67–3.45), lymph node dissection (RAMIE vs. OE: WMD = 1.56, −3.29–6.43; VATE vs. OE: WMD = 1.05, −2.24–4.53), or 3-year OS (VATE vs. OE: HR = 1.14, 0.70–1.85). RAMIE ranked highest for reducing complications (SUCRA = 52.5%), while OE showed shorter operative time (SUCRA = 94.0%). Achieving R0 resection ranking: RAE (SUCRA 47.3%), OE (SUCRA 43.8%), and VATE (SUCRA 8.9%). In lymph node dissection, OE had the highest probability of being superior (59.5%), markedly outperforming RAMIE (21.3%) and VATE (19.2%). Survival outcomes were comparable across all approaches.ConclusionsOE, VATE, and RAMIE demonstrate equivalent oncological efficacy in EC after neoadjuvant therapy. Perioperative advantages differ: RAE may lower complications, whereas OE offers procedural efficiency. Surgical selection should prioritize individualized risk-benefit assessment, anatomical considerations, and institutional expertise. Prospective trials are warranted to validate these findings and refine technique-specific indications.